Recent advances on coxsackievirus A6 vaccine research - Zhou, Xianfeng; Mo, Han; Li, Hui; He, Fenglan; Yang, Qian (Frontiers in Immunology, 2025)
BackgroundHand, foot, and mouth disease (HFMD) is an acute infectious disease caused by human enteroviruses (EVs). EVs are most prevalent in children under five years of age and have the potential to result in herpangina, HFMD, and severe complications, including encephalitis and death. Since the first outbreak was reported in 2008 in Finland, coxsackievirus A6 (CVA6) has spread rapidly and frequently undergone recombination events worldwide, posing a threat to the health of pediatric population around the globe.Aim of reviewThe dearth of vaccines and anti-CVA6 drugs hinders the efficient prevention and control of CVA6. However, over the course of the last decade, researchers have endeavored to develop potential vaccine candidates for CVA6 using various pathways. In this study, we present a systematic review of research progress pertaining to the CVA6 vaccines, with a particular emphasis on the most recent advancements in CVA6 vaccine development and evaluation. The objective of this review is to establish a theoretical foundation for the formulation of preventive and control strategies, as well as the development of vaccines against not only CVA6 but also other key serotypes in the future.Key scientific concepts of reviewThe review comprehensively addresses the diverse array of CVA6 vaccine development, encompassing a range of modalities such as inactivated, virus-like particle, and subunit vaccines, among others. A systematic analysis was conducted on animal-based assessments of various CVA6 vaccines, encompassing immunogenicity, protection rate, and cross-immunization as critical evaluation parameters. In light of the recurrent recombination of CVA6 and the evolution of pathogen profiles, the recommendation is made for the future development of multivalent and mRNA vaccines, which hold significant potential in the prevention and control of CVA6 and other major dominant serotypes.